Functionalization of graphene oxide via epoxide groups: a comprehensive review of synthetic routes and challenges - Gonçalves, Mayara G.; Costa, Vinícius O.; Martinez, André H. G.; Régnier, Bernardo M.; Gomes, Gabriel C. B.; Zarbin, Aldo J. G.; Orth, Elisa S. (Frontiers in Carbon, 2024)
Graphene oxide (GO) has attracted significant attention from the scientific community due to its mechanical, optical, electrical, and chemical properties. This review outlines synthetic methods for GO functionalization, including methods involving covalent and noncovalent bonds with organic molecules. In a novel contribution to this field, particular emphasis is placed on the functionalization via epoxy ring opening, an area that is still poorly studied and understood. First, we provide an overview of the basic structure and properties of graphene oxide. Subsequently, we explore the various methods employed to functionalize graphene oxide, noting the complexity of these reactions, which sometimes occur in a non-specific manner. However, there are some strategies for targeted functionalization. Furthermore, we present a critical analysis of the covalent functionalization through epoxy groups, demonstrating important aspects to be considered when choosing the reaction medium. The alkaline environment seems to favor this reaction, and this is a point of no consensus regarding the advantages and disadvantages of using basic pH in functionalization reactions. We also demonstrate some challenges involving the characterization and confirmation of the functionalization, mainly in the basal plane, and we show advances in the characterization techniques that can be further explored in future studies. Finally, some current challenges and future research directions are presented to contribute to the advancement in this field.